2019
DOI: 10.1139/apnm-2018-0675
|View full text |Cite
|
Sign up to set email alerts
|

Do stair climbing exercise “snacks” improve cardiorespiratory fitness?

Abstract: We investigated the effect of stair climbing exercise “snacks” on peak oxygen uptake. Sedentary young adults were randomly assigned to perform 3 bouts/day of vigorously ascending a 3-flight stairwell (60 steps), separated by 1–4 h of recovery, 3 days/week for 6 weeks, or a nontraining control group (n = 12 each). Peak oxygen uptake was higher in the climbers after the intervention (P = 0.003), suggesting that stair climbing “snacks” are effective in improving cardiorespiratory fitness, although the absolute in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 7 publications
2
46
0
3
Order By: Relevance
“…Figure 8 shows the variation in %HRR during the three games, which result in three intervals with high intensity, i.e., one per game. Even short durations of HIPA during work hours have been shown to significantly improve cardiorespiratory fitness [ 60 ]. Also, Gillen et al [ 11 ] showed that three cycling bouts of twenty seconds each at maximal intensity (i.e., one minute in total), performed within a ten minute period, resulted in similar effects on fitness, and indicators of muscular health, as efforts of moderate intensity performed for 50 min.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 8 shows the variation in %HRR during the three games, which result in three intervals with high intensity, i.e., one per game. Even short durations of HIPA during work hours have been shown to significantly improve cardiorespiratory fitness [ 60 ]. Also, Gillen et al [ 11 ] showed that three cycling bouts of twenty seconds each at maximal intensity (i.e., one minute in total), performed within a ten minute period, resulted in similar effects on fitness, and indicators of muscular health, as efforts of moderate intensity performed for 50 min.…”
Section: Discussionmentioning
confidence: 99%
“…Only one session of exercise is effective to transiently reduce capillary glycemia, insulin sensitivity, and ambulatory blood pressure in individuals with diabetes ( 35 , 50 ). In addition, the breaking up of sedentary behavior with very-short bouts of moderate- or high-intensity exercise throughout the day (“exercise snacks”) has shown several health-related benefits, including improvements in cardiorespiratory fitness ( 51 ), vascular function ( 52 ), glycemic control ( 53 ) and muscle function ( 54 ), being suggested as an effective strategy to prevent some deleterious effects of sedentary behavior and unhealthy food consumption ( 52 ). Indeed, the benefits of exercise snacks were reached by simple exercises using body weight (e.g.…”
Section: Physical Exercise For Managing Diabetes and Counteracting Dementioning
confidence: 99%
“…The concept of ‘exercise snacks’, whereby isolated, short bouts (∼20 s) of vigorous exercise can be incorporated into the day with several hours of rest in between (Jenkins et al . ; Little et al . ) is another interesting idea for moving brief vigorous exercise from the laboratory to the real‐world.…”
Section: Introductionmentioning
confidence: 99%